2015
DOI: 10.1002/app.42735
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E can be used to hinder scissioning in radiation cross‐linked UHMWPE during high‐temperature melting

Abstract: High-temperature melting (HTM) of ultrahigh molecular weight polyethylene (UHMWPE) was shown to improve its elongation and toughness. This was believed to be due to increased scissioning and increased diffusion of polymer chains. It was hypothesized here that the toughness of previously radiation cross-linked UHMWPEs could also be improved by HTM. To test this hypothesis, the wear resistance, tensile mechanical properties, and Izod impact strength of radiation cross-linked virgin (no additive) and antioxidant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…When radiation cross‐linked UHMWPE was HTM, it was shown that increasing exposure time and temperature increased the terminal VI, which is an indication of increased chain scissioning . An optimum window of operating temperature and HTM duration was observed, where toughness could be improved without sacrificing wear resistance to chain scissioning.…”
Section: Discussionmentioning
confidence: 99%
“…When radiation cross‐linked UHMWPE was HTM, it was shown that increasing exposure time and temperature increased the terminal VI, which is an indication of increased chain scissioning . An optimum window of operating temperature and HTM duration was observed, where toughness could be improved without sacrificing wear resistance to chain scissioning.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that if a large Vitamin E content is desired to combat oxidation due to free radicals associated with other external sources such as cyclic loads 38 or infiltration of the implant with oxidizing species, 39 then the UHMWPE must be subjected to higher radiation doses in order to counter the effects of reduced crosslink density and wear resistance. A larger radiation dose would however imply a larger reservoir of free radicals in the lamellar regions of HXLPEs, thereby requiring more Vitamin E. Therefore, alternate crosslinking processes 25 or alternate antioxidants, which do not suppress crosslinking to such a large extent, 40 may be preferred to conventional irradiation of HXLPEs at room temperatures containing Vitamin E. It must be recognized that the type of wear investigated in this study was primarily the generation of particulate wear and did not investigate other modes of wear such as those related to fatigue processes like delamination wear. Such wear modes would require more knee-like articulation, so the results of this study can only be interpreted in terms of slowing the rate of generation of wear particles of UHMWPE under hip-like articulation involving a multidirectional wear pattern.…”
Section: Wear Resistancementioning
confidence: 99%
“…7,8 It also accelerates the generation of particulate wear in joint components. [21][22][23][24][25][26][27][28] Vitamin E can either be blended into the UHMWPE resin prior to molding 29 or diffused into the implant after radiation. This initial increase in crosslinking indicated that it increases resistance of UHMWPE to wear and leads to the development of highly crosslinked UHMWPEs (HXLPEs), which were subjected to higher radiation doses of gamma or electron beam radiation (50-100 kGy dose range), not as a final sterilization step of the packaged implant but as a processing step for molded sheets and rods of UHMWPE, prior to the fabrication of the implant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that high temperature melting (HTM) of radiation cross‐linked UHMWPE at above 280°C can improve its toughness, presumably due to combined effects of controlled chain scissioning and increased inter‐granular diffusion . We hypothesized that homogenization of vitamin E‐doped, radiation cross‐linked UHMWPE at above 280°C could increase its toughness.…”
mentioning
confidence: 99%